SUKUK AND ISLAMIC BANKING FINANCING : THEIR IMPACTS ON THE REAL SECTOR - Budi Trianto; Masrizal Masrizal (Bank Indonesia, 2021)
Indonesia continues to strive to develop Islamic finance, especially its Islamic banking and sukuk, to support the real sector. The growth of Islamic finance in Indonesia is expected to encourage the development of the national economy. This study aims to investigate the impact of Islamic banking financing and sukuk financing on Indonesia’s industrial output. Applying the Autoregressive Distributed Lags (ARDL) framework to monthly data from January 2011 to December 2018, we find that Islamic bank financing contributes positively to the real sector in both the long and short term. In addition, we also document a positive long-run contribution of sukuk financing to industrial output. Indeed, over the long run, sukuk financing tends to have a greater real impact than Islamic banking financing. The results of the study imply that Islamic banking and sukuk play a vital role in supporting the real sector in Indonesia. Accordingly, recent initiatives by the country to further develop its Islamic finance are steps in the right direction.